2022
DOI: 10.1590/1980-265x-tce-2021-0332en
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Coaching Leadership Related to Practice Environment Within Primary Health Care

Abstract: Objective: to correlate the nurses’ self-perception and the perception of nursing aides regarding coaching leadership and the practice environment within Primary Health Care. Method: cross-sectional and correlational study addressing 150 nursing workers: 75 nurses and 75 nursing aides of 13 Basic Health Units located in the south of São Paulo, SP, Brazil. The Brazilian version of the Practice Environment Scale, Questionário de Autopercepção do Enfermeiro no Exercício da Liderança [Questionnaire on Self-Percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(30 reference statements)
0
3
0
2
Order By: Relevance
“…Com a chegada da pandemia, a enfermagem conseguiu tornar-se mais evidente, mostrando a importância desses profissionais não só nos cuidados diretos com os pacientes, mas também exercendo papéis de liderança. Uma participação ativa dos enfermeiros nos assuntos da instituição levou ao empoderamento desses profissionais 5,[17][18] .…”
Section: Discussionunclassified
“…Com a chegada da pandemia, a enfermagem conseguiu tornar-se mais evidente, mostrando a importância desses profissionais não só nos cuidados diretos com os pacientes, mas também exercendo papéis de liderança. Uma participação ativa dos enfermeiros nos assuntos da instituição levou ao empoderamento desses profissionais 5,[17][18] .…”
Section: Discussionunclassified
“…Nursing workers became more evident during the pandemic, showing their relevance not only in providing direct care to patients but also in occupying leadership positions. The active participation of nurses in institutions' affairs empowered these professionals 5,[17][18][19] .…”
Section: /14mentioning
confidence: 99%
“…A Brazilian study found a mean of 3.4 for this subscale, considering it is a private and accredited hospital focused on leadership development 9 . Participative leadership within the frontline team ensures workers feel safer and free to discuss situations that can be improved, especially in times of uncertainty, such as a pandemic 18 .…”
Section: /14mentioning
confidence: 99%
“…Com isso, reduzimos o cuidado a procedimentos biomédicos, ao invés de experimentá-lo como cura. Cindimos o prazer e a dor sob fórmulas infalíveis das ciências positivas da razão instrumental (coaching, psicologia cognitiva, outros) (27) . Sobrevivemos mutiladas(os) sob o discurso positivista que ratifica a histórica contradição entre cuidado e capitalismo, qual seja: para acumular, o capital depende do trabalho reprodutivo que desvaloriza e estigmatiza (5) .…”
Section: Cuidar Para Descuidar: Negatividade Como Crítica Discursivaunclassified